Dimensions of Inspirational Leadership: An Exploratory Factor Analysis in the School Settings - Shrestha, Milan (Journal of Research in Education, 2025)
School leadership addresses the challenges and threats of the school regarding the change process by inspiring and motivating teachers. This function of leadership is represented by inspirational leadership, which is composed of five dimensions according to Bass and Bass, 2008. Connecting to it, the researcher aims to determine the factors of inspirational leadership among teachers in a school setting. For this purpose, this study employed a cross-sectional survey and collected data via a structured questionnaire from 502 sample teachers. The sample teachers were identified by employing a multi-stage cluster sampling. Then, the collected data were analyzed through Exploratory Factor Analysis (EFA), and in the end, the results were reasoned with social exchange theory. Then, through EFA, this study retained five dimensions of inspirational leadership as intellectual stimulation, envisioning, managing impression, molding follower’s expectations, and Managing meaning. These five dimensions of inspirational leadership are related to the social exchange between schools and teachers. In line with this, the school leadership generates innovative ideas, visualizes the ideal outlook of the school, presents self as a role model, creates a belief system, and develops a sense of ownership among teachers by inspiring them. In return for this, teachers were inspired and perform a high job in the school.